The art of Shia Yih Yiing: Problematizing Malaysian multiculturalism / Tan Kim - Tan , Kim (2021)
"Malaysia, TrulyAsia" is the popular slogan used when it comes to promoting Malaysia as a tourist spot. We could see the descriptionofMalaysia overall as a country on the official tourism website,“ There is only one place where all the colours, flavours, sounds and sights of Asia come together–Malaysia.", multiculturalism is one of the keyselling points of Malaysia.Most often the media represent happy Malaysian multiculturalism, by focusing on the diverse cultures,the exotic traditions of multiple cultural identities, and how these cultural identities coexist together. However, as suggested by many scholars, the idea of multiculturalism is not at all unproblematic. In a glance, Shia Yih Yiing's artworks fit perfectly in to the government narrative of happy multiculturalism, there presentation of multiplecultural identities, coexisting in a harmonious setting. Nonetheless, through the reading of secondary resources as well as personal interviews with Shia Yih Yiing, she mentioned her attempt of incorporating poeticresistancestrategiesinherartwork,revealingherintentwasnottosimplyshowhappyMalaysian multiculturalism.Therefore,thisresearchattemptstoanalysesfurtherontherepresentationofthemultipleculturalidentitiesofMalaysia,withaspecialfocusonfairytaleasherpoeticresistance strategy, how she chosetorep resentthese Malaysian identitieswithspecificfairytalecharacter. An attempt will alsobemadetoproblematize Malaysian multiculturalismthrough the discussion of Malaysianmulticulturalism situation visa vis the specific choice of fairy tale charactersshehasusedtorepresentacertain cultural identity, as well as the in clusion and exclusion of a certain cultural identities in the representation.